Shu zi zhuan xing : qi ye po ju de 34 ge jin nang = Digital transformation game plan - O'Brien, Gary; Guo, Xiao; Mason, Mike (O'Reilly Media Inc. ; Ji xie gong ye chu ban she, 2021)
Detailed summary in vernacular field.